Enseigner les sciences de la nature avec le projet de paysage à l’ENSP Marseille - Audrey Marco; Véronique Mure; François Wattellier; Cécil’ Mermier; Alexandra Biehler (Projets de Paysage)
The article refers to the links established between courses in natural sciences and landscape architecture at the École nationale supérieure de paysage (ENSP) of Marseilles through two courses focusing on the environment. We examine the role of field trips and the pedagogical dialogue established between teachers in natural sciences and landscape architecture in learning about landscape architecture with nature. It is based on a shared perception of the teachers responsible for the targeted teaching sequences and on the pedagogical documents conceived and gives details on the organisation and content of the curriculum from 2011 to 2017 at the school. The reflexive analysis conducted shows how the pedagogical co-design and interdisciplinary mediation deployed in the sequences make it possible to create learning situations a cross between field practice and workshop activities and to thus nurture the perception, knowledge, description, and transformation of sites in environmental terms throughout the landscape design process.